Contributions of Iran and Turkey to the World Information Science Literature: A Comparative Study - Al, Umut; Afzali, Mehdi (Information World, 2006)
This article investigates the contributions of Iran and Turkey to the world information science literature. In this context, the study examines Iran and Turkey addressed publications in the Social Sciences Citation Index (SSCI). Total number of publications of two countries in the information science journals was 140; 85 from Turkey and the remaining 55 from Iran. When analyzed in ten- year time periods, the number of Iran addressed publications shows a kind of instability with certain rise and decline whereas the number of Turkey addressed publications appears to rise steadily. The most preferred information science journal for Iran is International Information & Library Review while for Turkey it is Scientometrics. More collaborative work is preferred by Turkish scholars than their colleagues in Iran. The majority of Iranian publications come from authors with a librarianship background whereas Turkish publications include authors with different backgrounds such as statistics, industrial engineering and physics. It is pointed out in this article that the number of publications from both countries does not match their potentials. In this respect, both countries need to increase their contributions and thus have a betterposi- tion in the world of information science.